Exploring counterfeit purchase behavior: Towards a unified conceptual framework - Sharma, Piyush; Chan, R. (Association for Consumer Research (ACR), 2011)
Prior research on counterfeit purchase behavior shows mixed findings, possibly because it focuses on the ‘direct’ and ‘independent’ effects of attitudes, ethical judgments, and subjective norms, and ignores the role of important constructs such as counterfeit proneness and product evaluations. This paper addresses these gaps with a unified conceptual framework with counterfeit proneness as a focal construct and product evaluation as a key mediator of the process of counterfeit purchase behavior. Using a study with 610 ethnic Chinese shoppers in Hong Kong across four product categories it shows that counterfeit proneness influences the attitudes, ethical judgments, and subjective norms about buying a counterfeit product, which in turn affect the evaluation of a counterfeit product and purchase intentions